Panorama of the bible: New Testament - Binz, Stephen J. (Liturgical Press, 2016)
"While every character, story, and book of Scripture is significant in itself, stepping back for a broad, panoramic view of the entire Bible helps us to take in and understand God's single, unified plan for human history. In this second of a two-part panorama of the Bible, noted Scripture scholar Stephen Binz shows us how all of the Bible's many parts fit together in a grand and awesome narrative. With a clear vision of this sweeping unity, we can then understand far better our own place within the storyline and our own personal role within the mission of God."--Back cover